Outpatient titration of carbidopa/levodopa enteral suspension (Duopa). (4th May 2017) - Pahwa, Rajesh; Lyons, Kelly E.
Abstract : Carbidopa/levodopa enteral suspension (CLES; Duopa) is a suspension or gel formulation of carbidopa/levodopa that is approved by the USA Food and Drug Administration for the treatment of advanced Parkinson's disease patients with motor fluctuations. CLES is delivered at a constant rate continuously throughout the day into the jejunum through an infusion pump via a PEG-J tube implanted surgically. The efficacy of CLES was established in the USA based on a randomized, double-blind, double-dummy, active controlled, parallel group and 12-week study, in which mean daily OFF time was reduced by 4.0 h, compared to 1.9 h with oral immediate release carbidopa/levodopa. The CLES hardware consists of a cassette containing the drug, a pump to deliver the drug and tubing to connect the PEG-J to the pump. It is critical to understand the appropriate conversion of the carbidopa/levodopa daily dosages to the CLES dosage and how to program the pump and titrate CLES to achieve the most effective dose. We describe one methodology for patient selection, outpatient titration and pump programming.